Seroprevalence and identification of pathogenic Leptospira in rodents from Kuala Lumpur wet markets, Malaysia - Noh, Mohamed Asyraf (2021)
Pathogenic Leptospira are spiral-shaped bacteria that causes leptospirosis in infected victim. It was reported to be isolated from many mammal species all over the world, including human, establishing leptospirosis as the most widespread zoonosis disease. This bacterium species is widely known for having rodents as their main reservoir host, residing in the host’s renal tubule and spread to the environment through their host’s urine. Malaysia has declared leptospirosis as notifiable disease in 2010 and there has been increasing reported cases annually since then. Due to this, there is a need for a complete list or database of pathogenic Leptospira that circulate in Malaysia. Therefore, this study is performed in hope to contribute and provide information towards that goal. The objective of this study is to determine the seroprevalence and species distribution of pathogenic Leptospira in rodents captured from Kuala Lumpur wet markets. Four wet markets in Kuala Lumpur were chosen as the sampling sites of this study, namely Pasar Pudu, Pasar Chow Kit, Pasar Datuk Keramat and Pasar Petaling Street, as per recommendation by Kuala Lumpur City Hall (Dewan Bandaraya Kuala Lumpur, DBKL). Sampling was performed by live trapping for the duration of 12 months in 2017. Each rodent caught was euthanised, morphologically identified and processed for the extraction of blood serum and kidney samples. Microscopic Agglutination Test (MAT) were performed on serum samples (against a panel of 24 live Leptospira serovar culture) for serology test, while kidney samples were processed and subjected to molecular screening test for pathogenic Leptospira detection and cultured in Ellinghausen-McCullough-Johnson-Harris (EMJH) medium for Leptospira isolation. For each culture medium that succeeded in growing Leptospira, they were morphologically confirmed as Leptospira cultures under dark field microscope and underwent molecular characterisation using six loci Multilocus Sequence Typing (MLST) test for Leptospira species identification. Sampling yields 144 live captured rodents, all identified as house rat or Rattus rattus. MAT gave 50/144 (34.72%) positive samples for leptospiral antibody in rodents, with the most prominent serovar detected being serovar Malaya, followed by IMR LEP 175. A total of 50/144 (34.7%) samples were detected as pathogenic Leptospira from molecular screening test. As for bacteria isolation, 23 out of 144 culture samples (15.97%) were successfully isolated, and from this, MLST analysis identified two Leptospira species, with 20/23 (87%) samples identified as Leptospira borpetersenii and the other remaining three (13%) samples were identified as ST149 Leptospira interrogans serogroup Bataviae serovar Bataviae strain Swart. The findings in this study present the evidence of pathogenic Leptospira presence which strive and actively circulating in the rodent population of Kuala Lumpur wet markets. Rodents are indeed the reservoir or maintenance host of pathogenic Leptospira in the urban, highly populated setting of Kuala Lumpur. Both serology and molecular screening test results indicate a high endemicity for leptospirosis if the rodent population is left unchecked, as control of Leptospira reservoir host is important for preventing future leptospirosis outbreaks in Kuala Lumpur.